REGULATING THE TERMINATION OF EMPLOYMENT OF ABSCONDING EMPLOYEES IN THE PUBLIC SECTOR AND PUBLIC EDUCATION IN SOUTH AFRICA: A PRELIMINARY VIEW - Adriaan van der Walt; David Abrahams; Thanduxolo Qotoyi (Obiter, 2016)
The issue that is addressed in this note is whether or not the provisions dealing with unexplained absence in the South African national and provincial public sector does not unreasonably limit the constitutional right to fair labour practices, and whether the provisions do not circumvent the essential provisions of Convention 158 of the ILO. The public service at local level is not affected, since the Public Service Act is not applicable to such employees. Such employees enjoy the same legal protection as private-sector employees. This note therefore explores how these issues may be addressed, by firstly considering the general legal position in relation to employees who are absent without leave as well as absconding employees. Secondly the “deemed dismissal” provisions in the public sector are discussed. Thirdly, the constitutionality of the “deemed dismissal” provisions are briefly considered. The note concludes by providing an analysis of the courts’ approach to this matter, as well as making certain recommendations regarding the way forward.